“Ghana is an eye opener”: Enlightened personhood and transnational education among British-Ghanaians - Abotsi, E (2018)
Based on multi-sited ethnographic research, this thesis examines the transnational parenting and educational strategies of British-Ghanaian families and their search for the “good life”. While anxieties over their children’s futures contribute to the parents’ decisions to either send their children or relocate to Ghana, this thesis argues that the parents are searching for the ideal learning environment to instil the values that they associate with West African concepts of enlightened personhood. These values, that include studiousness, resilience, discipline, respect for seniority, and (Christian) morals, are incorporated into the parents’ understanding of “seriousness” that they deem necessary for leading successful lives. The thesis traces how these attributes that underlie the parents’ discourse of “Ghanaian” values are, on an analytical level, an enmeshment of “modern”, middle-class, Christian modes of life with the Akan term anibuei (mature, cultured, enlightened). This occurred during encounters with missionaries who sought to convert Africans to Christianity. Such values continue to shape the educational process and parenting practices in Ghana and the diaspora. Notions of character-building hardships, Christian values and respect for seniority form the parents’ and schools’ constructions of the “serious” person. In close relation, but also in contention with the values that constitute the core of “seriousness”, is the notion of imitating Europeans, captured in the Akan term abrofosεm. This is deemed to be dangerous for raising successful African children. In the four ethnographic chapters, I attend to the values and aspirations that shape the parents’ pursuit towards desired lives. The first chapter examines the parents’ attempts at pursuing the “good life” through drawing on resources available in the UK and Ghana. The second chapter addresses how the young people from my research learned to value academic achievement. This chapter also explores how parents consciously made their children go through particular kinds of hardships in Ghana in order to expose them to situations that would help them develop resilience and aspire to be prosperous. I show that though the young people found these experiences challenging they embraced hardship as a challenge that ultimately contributes to their personal growth. The third chapter examines the tensions between the young people and school staff as both parties attempted to mark boundaries around “Ghanaian” values and what they perceived to be Western. The last ethnographic chapter explores how the young people coped with and attempted to resist practices such as corporal punishment and system of seniority among peers that they deemed unnecessary for their education. My thesis contributes to debates in transnational parenting and educational strategies by showing how the parental cultivation of seriousness is part of a wider search for the “good life”. I suggest that these practices are embedded in historical processes of creating transnationally mobile middle-class Ghanaians. Consequently, I reveal ongoing tensions between “Ghanaian” values and what is perceived to be mimicking Europeans. Through the young people’s experiences of schooling in Ghana, this thesis traces how a new generation is negotiating expectations of successful adulthood which are, at times, discordant with their parents’ and the schools’ visions of the educated person.